Advancing book clubs as non-formal learning to facilitate critical public pedagogy in organizations. Issue 3 (July 2022) - Grenier, Robin S; Callahan, Jamie L; Kaeppel, Kristi; Elliott, Carole
Book clubs are a well-known form of social engagement and are beneficial for those who take part, yet book clubs are not fully realized within management as a site for learning. This is unfortunate because book clubs that read fiction can foster social processes and help employees in search of more critical and emancipatory forms of learning. We theoretically synthesize the literature to advance current thinking with regard to book clubs as critical public pedagogy in organizations. We begin by introducing book clubs as non-formal adult learning. Then, book clubs that employ fiction as a cultural artifact are presented as a way for members to build relationships, learn together, and to engage in cultural change work. Next, the traditional notions of book clubs are made pedagogically complex through the lens of critical public pedagogy. Finally, we offer two implications: (1) as public pedagogy, book clubs can act as an alternative to traditional learning structures in organizations; and (2) book clubs, when valued as public pedagogy, can be fostered by those in management learning and HRD for consciousness raising and challenging existing mental models in their organizations.